"The Drug Use Unfortunately isn't all Bad": Chronic Disease Self-Management Complexity and Strategy Among Marginalized People Who Use Drugs. (May 2022) - Boucher, Lisa M.; Shoemaker, Esther S.; Liddy, Clare E.; Leonard, Lynne; MacPherson, Paul A.; Presseau, Justin; Martin, Alana; Pineau, Dave; Lalonde, Christine; Diliso, Nic; Lafleche, Terry; Fitzgerald, Michael; et al.
Self-management programs improve health outcomes and self-management is recommended for chronic conditions. Yet chronic disease self-management supports have rarely been applied to people who use drugs (PWUD). Thus, our objective was to explore self-management experiences among marginalized PWUD. We used community-based participatory methods and conducted qualitative interviews. Participants self-identified as having long-term and past year experience using non-prescribed drugs, one other chronic condition, and socioeconomic marginalization. We analyzed the data using reflexive thematic analysis. Although many participants considered drug use a chronic health issue, self-medicating with non-prescribed drugs was also a key self-management strategy to address other health issues. Participants also described numerous other strategies, including cognitive and behavioral tactics. These findings highlight the need for a safe supply of pharmaceutical-grade drugs to support self-management among marginalized PWUD. Self-management supports should also be tailored to address relevant topics (e.g., harm reduction, withdrawal), include creative activities, and not hinder PWUD's agency.